The Pattern of Musculoskeletal Cancers in Pakistan - Memon, Sikander Munir; Mangi, Fayaz Hussain; Memon, Faheem Ahmed; Sushel, Champa; Shaikh, Abdul Ghani; Shaikh, Tanweer Ahmed (Journal of Liaquat University of Medical & Health Sciences, 2022)
Objective: The study aimed to assess the pattern of musculoskeletal cancers in the Pakistani population who visited NIMRA hospital situated at Jamshoro. Methodology: It was an observational retrospective study conducted at the Nuclear Institute of Medicine and Radiotherapy (NIMRA) and LUMHS, Jamshoro, from August 2019 to December 2020. A total of 626 patients were selected for this study. The data regarding patients were sourced from NIMRA, LUMHS Jamshoro. All the patients of both genders and ages diagnosed at NIMRA with any cancer were included in the study. Patients who did not return for follow-up after their metastatic and laboratory tests were excluded from the study. A Chi-square test was conducted to assess the association between diagnosed cancers versus gender and age groups. The confidence interval was set at 95%, and the probability value ?0.05 was statistically significant. Results: A total of 626 patients were selected for this study. Of them, 362 (57.8%) were males and 264 (42.2%) were females, with a mean age of 34.67 years and a standard deviation of 18.998. The most prevalent cancer is soft-tissue sarcoma (STS) 129 (20.6%), followed by chondrosarcoma 119 (19%), and osteosarcoma 91 (14.5%). Forty percent of the cancers were diagnosed as stage II, followed by stage III (22%), stage IV (22%) and stage-I (16%), respectively. A significant association between diagnosed cancers were found with gender (p=0.001) and age group (p=<0.001). Conclusion: Soft-tissue sarcoma, chondrosarcoma, and osteosarcoma are the most common musculoskeletal cancers in the Pakistani population. Key Words: Chondrosarcoma, Ewing sarcoma, Musculoskeletal Cancers, Osteosarcoma, Rhabdomyosarcoma, Soft-tissue sarcoma.